QUALITY ASSURANCE OF TILAPIA FISH (Oreochromis niloticus) FRESHNESS WITH TREATMENT OF WEEDING - Taufik Hidayat (University of Sultan Ageng Tirtayasa, 2020)
Fresh fish is a fish that has the same properties as live fish, both in appearance, smell, taste and texture. This research aimed to determine the quality of a fishery product. This research aimed to determine the freshness test of tilapia in a sensory way and see the different characteristics of different fish conditions. Method research measured yield, morphometric, and organoleptic. The treatment used was low temperature. Low temperature storage (0-5 oC) in tilapia (Oreochromis niloticus) by treatment without weeding can reduce the rate of deterioration in post-death tilapia quality even though the results are not significant with the average organoleptic value of tilapia freshness which is 7-9 in the range of days 0-2.